Implementing internet-delivered cognitive behavioral therapy in healthcare services: a qualitative exploration of stakeholder experience - Duffy, Daniel; Richards, Derek; Earley, Caroline; Timulak, Ladislav (Frontiers in Digital Health, 2023)
Background This study consisted of a qualitative exploration of stakeholder experience regarding the implementation of internet-delivered cognitive behavioral therapy (iCBT) as part of routine service provision within the UK's Improving Access to Psychological Therapies program. Methods Stakeholder groups included service providers (n = 6), commercial iCBT representatives (n = 6) and patients who received a course of iCBT as part of treatment at the service (n = 7). Participants took part in a semi-structured interview over the telephone, and subsequent data were qualitatively analyzed using the descriptive-interpretive approach. Results Service providers highlighted the importance of effective leadership and management, training initiatives, the provision of feedback to commercial iCBT representatives and creating work structures around iCBT to facilitate iCBT supporting staff in their use of it. Commercial iCBT representatives similarly reported the importance of training clinicians in iCBT use, identifying the appropriate individuals at all levels of the service to drive iCBT implementation, and the importance of being responsive to any problems or needs that arise from the service. Patients reported an overall positive experience of receiving iCBT but highlighted a need for more information from their supporter and the intervention to better structure their usage. Contextual factors, in terms of barriers and facilitators, were also highlighted by service provider and commercial participants; citing negative clinician attitudes and technological issues/bugs as barriers to implementation, and the exposure to iCBT created by COVID-19 and perseverance in using iCBT over time as facilitators. Discussion The findings contribute to a growing field of literature that seeks to understand the experience of relevant stakeholders who are involved with and contribute to iCBT implementation, including commercial iCBT representatives who, to our knowledge, have not been accounted for as part of published research to date.